Bioeconomic considerations of culture-based fisheries in Sri Lankan reservoirs - Petersen, E.H.; Digamadulla, D.S.; Adikari, A.M.A.N.; Amarasinghe, U.S.; De Croos, M.D.S.T.; Jones, C.M. (Australian Center of International Agricultural Research, 2026)
The project highlights a number of key findings that can be applied to enhance the profitability and sustainability of Sri Lankan culture-based fisheries (CBF). The 2 main decision variables for the management of these fisheries are fishing intensity and stocking density. Strict government regulations are providing a strong institutional environment to allow effective management of fishing intensity (a rare thing for CBF globally) which is leading to the profitability of these enterprises. With these regulations in place, fi shing intensity is largely managed by the number of fishing licences issued by reservoir fishing organisations (RFOs). Our research suggests that reservoirs are generally profitable if fishing intensity is restricted to less than 0.13 boats/ha/day (46 boats/ha/year). When holding fishing intensity under this level, the main lever for managing the profitability of the fishery is then stocking density.Currently, the management of stocking densities in CBF of Sri Lanka is ad hoc. Ideally, the coordination of stocking programs would be led by a collective of leaders from reservoir fisheries organisations, supported by the National Aquaculture Development Authority (NAQDA), and would include transparent reservoir-specific decisions on stocking densities of various species based on the size of the reservoir.Generally, major reservoirs are more profitable that medium or minor reservoirs due to economies of scale. Stocking in major reservoirs is often not needed, whereas medium reservoirs are profitable with a stocking density of greater than 3,000 post larvae (PL)/ha/year, and with higher stocking densities of between 5,000 and 15,000 PL/ha/year for minor reservoirs. When considering individual fish species, inefficiency in the production of tilapia and carp is mainly due to inefficiencies in stocking density, whereas inefficiencies in the production of giant freshwater prawn (GFP) is due to inefficient fishing techniques. A change of harvest technology rather than stocking densities is recommended for GFP. Stocking of tilapia in major reservoirs is often not needed, but stocking densities above 1,000 PL/ha/year for medium and minor reservoirs is recommended. There is significant scope for profit improvements with increased intensification of carp. We recommend stocking densities for carp above approximately 300, 600 and 1,000 PL/ha/year for major, medium and minor reservoirs, respectively.
Keywords: Bioeconomics; Inland fisheries; Culture-based fisheries; Value chain